THE EFFECT OF HIGH FAT DIET ON THE CONCENTRATION RATIO BETWEEN PROOXIDANT AND TOTAL ANTIOXIDANT IN RAT (Sprague dawley) - Guntari Titik Mulyani; Hastari Wuryastuti (Jurnal Sain Veteriner, 1999)
The objective of the investigation was to study the relationship between ratio prooxidant and total antioxidant (peroxidation index) and cell damage in male rats. Fourty male Sprague dawley rats, 3 month of age, 150-200 g of body weight were alloted randomly to 2 groups of 20 each. The first group was fed normal diet (control), the second group was fed high fat diet (20% fat). After 2 weeks, the blood samples were taken out from 5 rats of each group for measuring prooxidants and antioxidants. The prooxidants and anti-oxidants st-atus in this study was done by measuring thio barbituric add subs tance I TEARS) and total antloxldant status (TAS) concentration. The heart, liver and kidney tissues were collected for histopatological analysis, Peroxidation index (PI) were determined by dividing TBARS value with TAS value. The same procedures were repeated after 4, 8, and 16 weeks. Analysis of the data showed that after 16 weeks on experimental diet, the mean concentration of TBARS in blood of group I was 1.45Q+G.158 umol/L and the mean concentration of TBASS in blood of group 11 was 4,75 + 2,17 nmol/L. The highest ratio between prooxidant and total antioxidant was 17.47 and the Lowest ratio between oxidant and total antioxidant was 0.849. Analysis of histopatology showed that there were hyalinitation and oardiomyopathy in the heart tissu, fatty liver degeneration and necrosis in the liver and necrose and atrophy of the kidney. From the results can be concluded that (1) feeding high fat diet induced high ratio between proojiidant and antioxidant con^ centration (peroxidation Index). (2) Cell damage can be caused by high peroxidation index. (3) Individual variation might be caused by genetic factor.